Authentic Research in the Classroom Increases Appreciation for Plants in Undergraduate Biology Students. (29th May 2021) - Hiatt, Anna C; Hove, Alisa A; Ward, Jennifer Rhode; Ventura, Liane; Neufeld, Howard S; Boyd, Amy E; Clarke, H David; Horton, Jonathan L; Murrell, Zack E
Synopsis: Engaging students in authentic research increases student knowledge, develops STEM skills, such as data analysis and scientific communication, and builds community. Creating authentic research opportunities in plant biology might be particularly crucial in addressing plant awareness disparity (PAD) (formerly known as plant blindness), producing graduates with botanical literacy, and preparing students for plant-focused careers. Our consortium created four CUREs (course-based undergraduate research experiences) focused on dual themes of plant biology and global change, designed to be utilized by early and late-career undergraduates across a variety of educational settings. We implemented these CURES for four semesters, in a total of 15 courses, at four institutions. Pre- and post-course assessments used the Affective Elements of Science Learning Questionnaire and parts of a "plant blindness" instrument to quantify changes in scientific self-efficacy, science values, scientific identity, and plant awareness or knowledge. The qualitative assessment also queried self-efficacy, science values, and scientific identity. Data revealed significant and positive shifts in awareness of and interest in plants across institutions. However, quantitative gains in self-efficacy and scientific identity were only found at two of four institutions tested. This project demonstrates that implementing plant CUREs can produce affective and cognitive gains across institutional types and course levels. Focusing on real-world research questions that capture students' imaginations and connect to their sense of place could create plant awareness while anchoring students in scientific identities. While simple interventions can alleviate PAD, implementing multiple CUREs per course, or focusing more on final CURE products, could promote larger and more consistent gains in student affect across institutions.